PELATIHAN PENGELASAN BAGI MASYARAKAT PEKERJA LEPAS GALANGAN KAPAL DI JAWA TENGAH - Samuel Febriary Khristyson; Sarwoko Sarwoko; Sulaiman Sulaiman; Bambang Sri Waluyo; Indro Dwi Cahyo; Albin Abdur Razaq; Mikahael Fernandus (Sekolah Vokasi Universitas Diponegoro, 2021)
Central Java province has several industries that have various kinds of competencies that must be mastered by every worker. The potential of vocational schools in Indonesia. Increasing the competence of human resources is to increase the choices that humans have. The higher the education, the more opportunities that can be achieved. The purpose of this paper is to explore and facilitate activities to improve the skills of the freelancer community in the shipbuilding industry in Central Java. The method used is the method of collecting data for experiments . By compiling the experimental setting data used, it is adjusted to the reading of the data from the welding process and endeavored to be processed properly. The result with the experimental method is obtained a schematic stage of the welding process with SMAW. By paying attention to the amperage and voltage settings when the welding process is adjusted to pre-preparation before the welding process, good welding results are also obtained so that when visually inspected there are no visible defects in the welding results. However, in the application process, it is necessary to look at the flight time of freelancers in the welding field and the welding position.